Trademark Valuation According to Laws and Regulations in Vietnam - Nam, Tran Van; Quynh, Nguyen Thi Nhu; Huy, Dinh Tran Ngoc; Chung, Pham Duc; Ha, Tran Vu Nhat (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Pricing and valuation may be confusingly interchangeable in various industries from manufacturing to commerce etc.. However, they are in fact different. Pricing can be simply understood as a process whereby the price is set by a seller or by an agreement between a seller and a buyer. On contrary, valuation analysis is normally conducted by experts. So, trademark valuation is a process whereby a trademark value is determined by means of diligent research, unbiased judgment, and some pretty simple arithmetic. In this study, we point out the drawbacks and obstacles in pricing in trademark transfer in our country in comparison with other countries/regions and then we will suggest some measures to improve the regime for pricing in trademark transfer in Vietnam. Authors also present Some Basic Concepts Related to Pricing And Valuation Of Trademark and valuation methods. Authors also use a construction case of LICOGI (general company in construction and infrastructure in Vietnam) as reference for pricing issues. Last but not least, in this study we could resolve some controversial issues in trademark pricing and transfer in various companies from production, manufacturing to construction, real estate and commerce sectors in developing countries such as Vietnam, at least from definitions, concepts and legal framework.Keywords: Intellectual Property Assets; Trademark Pricing Services; Law; Valuation Method; Vietnam Penilaian Merek Dagang Menurut Undang-Undang dan Peraturan di Vietnam Abstrak Penetapan harga dan penilaian mungkin membingungkan dan dapat dipertukarkan di berbagai industri mulai dari manufaktur hingga perdagangan, dll. Namun, sebenarnya keduanya berbeda. Penetapan harga secara sederhana dapat dipahami sebagai proses di mana harga ditetapkan oleh penjual atau dengan kesepakatan antara penjual dan pembeli. Sebaliknya, analisis penilaian biasanya dilakukan oleh para ahli. Jadi, penilaian merek dagang adalah proses di mana nilai merek dagang ditentukan melalui penelitian yang rajin, penilaian yang tidak bias, dan beberapa aritmatika yang cukup sederhana. Dalam studi ini, kami menunjukkan kelemahan dan hambatan dalam penetapan harga dalam transfer merek dagang di negara kami dibandingkan dengan negara/kawasan lain dan kemudian kami akan menyarankan beberapa langkah untuk meningkatkan rezim penetapan harga dalam transfer merek dagang di Vietnam. Penulis juga menyajikan Beberapa Konsep Dasar Terkait Penetapan Harga Dan Penilaian Merek Dagang dan metode penilaian. Penulis juga menggunakan kasus konstruksi LICOGI (perusahaan umum dalam konstruksi dan infrastruktur di Vietnam) sebagai referensi untuk masalah harga. Last but not least, dalam penelitian ini kita dapat menyelesaikan beberapa masalah kontroversial dalam penetapan harga dan transfer merek dagang di berbagai perusahaan mulai dari produksi, manufaktur hingga konstruksi, real estat dan sektor perdagangan di negara-negara berkembang seperti Vietnam, setidaknya dari definisi, konsep dan kerangka hukum. .Kata kunci: Aset Kekayaan Intelektual; Layanan Penetapan Harga Merek Dagang; Hukum; Metode Penilaian; VietnamОценка товарного знака в соответствии с законами и правилами Вьетнама АннотацияЦенообразование и оценка могут быть ошибочно взаимозаменяемы в различных отраслях, от производства до торговли, и т. д. Однако на самом деле это разные понятия. Ценообразование может быть просто понято как процесс, посредством которого цена устанавливается продавцом или соглашением между продавцом и покупателем. Напротив, оценочный анализ обычно проводится экспертами. Таким образом, оценка товарного знака — это процесс, в ходе которого стоимость товарного знака определяется посредством тщательного исследования, беспристрастного суждения и некоторых довольно простых арифметических действий. В этом исследовании мы указываем на недостатки и препятствия в ценообразовании при передаче товарных знаков в нашей стране по сравнению с другими странами/регионами, а затем предлагаем некоторые меры по улучшению режима ценообразования при передаче товарных знаков во Вьетнаме. Авторы также представляют некоторые основные концепции, связанные с ценообразованием и оценкой товарных знаков, и методы оценки. Авторы также используют случай строительства LICOGI (генеральная компания в области строительства и инфраструктуры во Вьетнаме) в качестве справочного материала по вопросам ценообразования. И последнее, но не менее важное: в этом исследовании мы смогли решить некоторые спорные вопросы, связанные с ценообразованием и передачей товарных знаков в различных компаниях из производственного сектора, изготовления в сектор строительства, недвижимости и торговли в развивающихся странах, таких как Вьетнам, по крайней мере, в отношении определений, концепций и правовой базы.Ключевые слова: Активы интеллектуальной собственности; Услуги по ценообразованию товарных знаков; Закон; Метод оценки; Вьетнам